Attitudes, beliefs and common practices of hand therapists for base of thumb osteoarthritis in Australia (The ABC Thumb Study). (March 2018) - Duong, Vicky; Bennell, Kim L; Deveza, Leticia A; Eyles, Jillian P; Hodges, Paul W; Holden, Melanie A; Hunter, David J; Jongs, Ray; Knapp, Donna; Mei, Yifang; Vicenzino, Bill; Wajon, Anne; et al.
Introduction: The purpose of this study was to identify attitudes, beliefs and common practices of hand therapists in Australia regarding assessment and management of base of thumb osteoarthritis. Methods: Monthly emails with a link to a 57-item cross-sectional survey were sent to members of the Australian Hand Therapy Association between November 2015 and February 2016. The survey included a case scenario of a patient with base of thumb osteoarthritis with questions about assessment and non-pharmacological and non-surgical treatment interventions for this case. Participants also rated their agreement with a series of 20 attitude and belief statements on a 6-point Likert scale. Data underwent descriptive analysis. Results: A total of 124 therapists accessed the survey, of which 77 (62%) returned completed answers and 47 (38%) partially completed it. The majority were occupational therapists (n = 92, 74%), and the remaining were physiotherapists. The most common clinical assessment methods used for base of thumb osteoarthritis were palpation (96%), range of motion (90%), the grind test (85%), and pain on opposition across the palm (82%). The commonly reported treatments included a combination of orthosis prescription (92%), pain education (78%), heat (75%) and exercise (74%). Conclusion: The findings highlight commonly used assessment tools and treatments for a typical patient with base of thumb osteoarthritis. Despite the low response rate, there is consistency among general treatment for base of thumb osteoarthritis. Variation exists within the specifics of exercise and orthosis prescription. The results of the survey reflect the lack of standardised recommendations for the management of base of thumb osteoarthritis.